The loss of 1p as a reliable marker of progression in a child with aggressive meningioma: a 16-year follow-up case report - Hemmer, Sina; Sippl, Christoph; Sahm, Felix; Oertel, Joachim; Urbschat, Steffi; Ketter, Ralf (Pediatric neurosurgery, 2021)
Background: Here, we present the case of a 32-year-old female with a progressing history of meningioma for 16 years starting with an ethmoidal lesion in 2002. The initial tumor specimen of this patient showed a deletion of the short arm of chromosome 1 through a translocation between chromosomes 1 and 11 (t[1; 11]) as well as additional chromosomal aberrations, including partial or complete monosomy of chromosomes 2, 6, 7, 11, 13, and 22. These molecular characteristics were already known to be associated with an aggressive course of the disease, and the patient was, therefore, included in a strict follow-up regime. From 2003 to 2019, the patient suffered multiple relapses and consecutive tumor resections. Methods: Tumor specimen from 2017 was examined using a genome-wide methylation analysis as well as a whole-genome sequencing. Results: These analyses confirmed the findings of 2002 and proved genetic alteration in the meningioma to be very stable over the time. Yet SMO and AKT1 mutations, which have been described to be paradigmatic in frontobasal meningioma, could not be found. Conclusions: Genetic characteristics seem to be very stable during progression of the disease. The loss of 1p represents to be a potential marker for the poor clinical course of our child meningioma. In 2019, our patient passed away due to the progress of her meningioma disease.